Wellness in the invisible workforce: a pilot well-being study in black, indigenous, and people of color (BIPOC) women faculty in the pharmacy and pharmaceutical sciences - Suzanne C. Harris; Matthew Shane Loop; Kaniz Afroz Tanni; Klarissa D. Jackson; Carla Y. White (BMC Medical Education)
Abstract Background Black, Indigenous, and other People of Color (BIPOC) women faculty are underrepresented in biomedical sciences and higher education. This disparity has been highlighted in previous studies to harm productivity, career progression, and well-being. This pilot study aimed to assess the perceived impact of a longitudinal well-being program for BIPOC women faculty, estimating its effects on well-being, burnout, and self-efficacy. Methods Full-time faculty in pharmacy or pharmaceutical science, identifying as BIPOC women, participated in this pilot repeated cross-sectional study of participants in a Well-Being Initiative, with the first cross-sectional study coming before a pilot intervention and the second cross-sectional coming after the pilot intervention. Cohort 1 engaged in a two-year program, while Cohort 2 participated for one year. Open-text questions assessed program impact on well-being, and inductive coding identified themes. Well-being, burnout, and self-efficacy were measured using the General Well-Being Index (WBI), Maslach Areas of Worklife Survey (AWS), 2-items from the Maslach Burnout Index-Human Services Survey (MBI-HSS), and General Self-Efficacy Survey (GSES). Descriptive statistics were calculated for primary and secondary outcomes. Results Sixteen participated in Cohort 1, and 18 participated in Cohort 2. Both cohorts reported a positive impact on well-being and a sense of community as a result of the program. Post-intervention median WBI decreased, and burnout and well-being risk declined (MBI: 24% and 28% point decrease at risk for burnout, WBI: median score 4 to 3 with 20% decreased risk for poor well-being, and median score 3 to 0.5 with a 61% point decrease at risk for poor well-being, for Cohorts 1 and 2, respectively). The AWS community subscale (Cohort 1) median score increased from 2.67 to 3.5, and values subscale (Cohort 2) median score increased 3.17 to 3.67, the largest increases. Cohort 2 exhibited improved self-efficacy (GSES median score change of 30 to 34). Participants reported the sense of community and connection built over the year(s) of the program, the ability to share of experiences from those further along in their career, having a safe space to be authentic with fellow participants, and the various sessions on creating self-care plans and maintaining core values as top themes of how program most benefited their well-being. Lessons learned and opportunities for improvement are addressed. Conclusion Participants reported many of the key impacts were the program’s ability to foster a sense of community and help them develop skills for personal and professional well-being. While higher baseline risks of poor well-being and burnout persist for BIPOC women faculty, positive trends emerged post-intervention. This study contributes to innovative strategies focused on supporting the well-being of BIPOC women faculty and lessons learned may inform and help refine future research. Clinical trial number Not applicable